(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: This study aimed to describe the current use of artificial intelligence (AI) tools in learning among medical students at Hanoi Medical University in 2025 and to examine factors associated with frequent AI use. Methods: A cross-sectional study was conducted among 400 full-time undergraduate medical students. Data were collected using a self-administered online questionnaire developed on the REDCap platform, covering demographic characteristics, academic information, information technology competence, AI knowledge level, and patterns of AI use in learning. Descriptive statistics and Chi-square tests were used for data analysis. Results: AI tools were widely used in learning among medical students, primarily for information retrieval, translation of academic materials, and learning support. Frequent AI use was significantly associated with gender, year of study, information technology competence, and level of AI knowledge. Conclusions: AI tools are widely adopted by medical students to support learning activities. The findings highlight the need to strengthen digital skills training and provide appropriate guidance to promote effective and responsible use of AI in medical education.